Evaluation of the MRL Diagnostics Dengue Fever Virus IgM Capture ELISA and the PanBio Rapid Immunochromatographic Test for Diagnosis of Dengue Fever in Jamaica - Palmer, Carol J. (American Society for Microbiology, 1999)
We evaluated two new commercial dengue diagnostic tests, the MRL Diagnostics Dengue Fever Virus IgM Capture ELISA and the PanBio Rapid Immunochromatographic Test, on serum samples collected during a dengue epidemic in Jamaica. The MRL ELISA method correctly identified 98% (78 of 80) of the samples as dengue positive, while the PanBio test identified 100% (80 of 80). Both tests were 100% (20 samples of 20) specific.